2014
DOI: 10.5901/mjss.2014.v5n16p409
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between the Clothing and Textiles Curriculum and the World of work

Abstract: The delivery of the Clothing and Textiles curriculum has been marred by a myriad of challenges, and this has not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition to the mastery of specific technical skills such as pattern making, sewing, and drawing, authors highlight the need for employability competencies. This includes teamwork, communication, solving complex problems, self-management, and lifelong learning, as emphasized by Boahin and Hofman (2013), Muzenda and Duku (2014), and Yamada and Otchia (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the mastery of specific technical skills such as pattern making, sewing, and drawing, authors highlight the need for employability competencies. This includes teamwork, communication, solving complex problems, self-management, and lifelong learning, as emphasized by Boahin and Hofman (2013), Muzenda and Duku (2014), and Yamada and Otchia (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The development of competencies, skills, and attitudes related to employability provides individuals with flexibility and adaptability to meet the constant changes in the world of work (Boahin & Hofman, 2013). Higher education curricula have increasingly focused on the development of competencies, especially professional competencies (Hodges et al, 2015), offering a possible solution to bridge the gap between graduates' qualifications and the demands of the workforce (Muzenda & Duku, 2014). Competencies in this context include proactivity, creativity, problem-solving, teamwork, interpersonal, social and critical thinking, communication, and networking (Boahin & Hofman, 2013).…”
Section: A Closer Look At the Competencies Of The Fashion Designermentioning
confidence: 99%
See 2 more Smart Citations
“…It was also important to realize that efforts were underway to integrate industrial training in the other category, because industrial attachment has become part and parcel of education and training in the field of clothing and textiles. Adequacy of periods of industrial training is important since Muzenda and Duku (2014) have observed that contact hours in Clothing & Textiles programmes usually involve more theory to the neglect of industrial attachment. As a result, according to Muzenda and Duku, such students become ill-equipped to match with employment in the world of work.…”
Section: Different Industrial Attachment Practicesmentioning
confidence: 99%